Three-Year Follow-Up of a Prospective, Double Blinded Multi-Center RCT Evaluating DBS with a Multiple Source, Constant-Current Rechargeable System for Treatment of Parkinson's Disease (INTREPID). (16th November 2020) - Starr, Philip A; Tröster, Alexander; Schrock, Lauren; House, Paul A; Giroux, Monique; Hebb, Adam O; Farris, Sierra; Whiting, Donald M; Lechliter, Timothy; Ostrem, Jill L; Palenzuela, Marta S.L; Galifianakis, Nicholas; et al.
Abstract: INTRODUCTION: Subthalamic Deep Brain Stimulation (STN-DBS) is an established therapeutic option for managing the motor symptoms of Parkinson's disease (PD); however, it has not been previously evaluated in a double-blind, randomized controlled trial (RCT) with sham control. METHODS: INTREPID (Clinicaltrials.gov identifier: NCT01839396) is a multi-center, prospective, double-blinded randomized controlled trial (RCT) sponsored by Boston Scientific. Subjects with advanced PD were implanted bilaterally in the STN with a multiple-source, constant-current DBS system (Vercise, Boston Scientific). Subjects were randomized to either receive active versus control settings for 12 weeks. Upon completion of the 12-week blinded period, subjects received their best therapeutic settings in the open-label phase up to 5 years. During long-term follow-up, motor improvement and quality of life was evaluated using UPRDS, PDQ39, Schwann and England, etc. Adverse events were also collected. RESULTS: The study met the primary endpoint demonstrated by a mean difference of 3.03 ± 4.52 hours (p < 0.001) between active and control groups in ON time without troublesome dyskinesia and with no increase in antiparkisonian medication, from post-implant baseline to 12-weeks post-randomization. At 2 years, a 46% improvement in UPDRS III scores was reported (sustained since last follow-up at 1 year) and overall improvement in quality of life was maintained compared to pre-surgery screening. Three-year follow up data will be presented. CONCLUSION: Results of the INTREPID RCT demonstrate that use of a multiple-source, constant current DBS system is safe and effective for treatment of PD motor symptoms. Long-term follow up on the use of this system and associated outcomes will be presented.